E-LEARNING IN BUSINESS - Woźniak-Zapór, Marta (International Journal of Economic Practice and Policy, 2013)
Training for employees improves work efficiency and for this reason companies should invest in their employees’ development. Realising the training necessity is, however, only the beginning. The choice of an appropriate training leaves much doubt. Yet, choosing a method of education is the most difficult part of the process. Apart from traditional training – which is still the most popular one – Internet training gains in popularity. The choice between an e-learning and a traditional training happens to be complicated. It depends on many factors – the size of a company and its needs. A small company that needs a training for a few employees will need completely different solutions from a corporation which, having hundreds or thousands of employees to be trained, may find it beneficial to organise an internal training, information and communication system. This article shows advantages and disadvantages of both traditional and e-learning training, which should be considered by companies choosing methods of their employees’ training.